‘Come together’—The Regulatory Interaction of Herpesviral Nuclear Egress Proteins Comprises Both Essential and Accessory Functions - Sigrun Häge; Manfred Marschall (Cells, 2022)
Herpesviral nuclear egress is a fine-tuned regulatory process that defines the nucleocytoplasmic release of viral capsids. Nuclear capsids are unable to traverse via nuclear pores due to the fact of their large size; therefore, herpesviruses evolved to develop a vesicular transport pathway mediating the transition across the two leaflets of the nuclear membrane. The entire process involves a number of regulatory proteins, which support the local distortion of the nuclear envelope. In the case of the prototype species of β-Herpesvirinae, the human cytomegalovirus (HCMV), the nuclear egress complex (NEC) is determined by the core proteins pUL50 and pUL53 that oligomerize, form capsid docking lattices and mediate multicomponent assembly with NEC-associated viral and cellular proteins. The NEC-binding principle is based on the hook-into-groove interaction through an N-terminal hook-like pUL53 protrusion that embraces an α-helical pUL50 binding groove. Thus far, the function and characteristics of herpesviral core NECs have been well studied and point to the groove proteins, such as pUL50, as the multi-interacting, major determinants of NEC formation and egress. This review provides closer insight into (i) sequence and structure conservation of herpesviral core NEC proteins, (ii) experimentation on cross-viral core NEC interactions, (iii) the essential functional roles of hook and groove proteins for viral replication, (iv) an establishment of assay systems for NEC-directed antiviral research and (v) the validation of NEC as putative antiviral drug targets. Finally, this article provides new insights into the conservation, function and antiviral targeting of herpesviral core NEC proteins and, into the complex regulatory role of hook and groove proteins during the assembly, egress and maturation of infectious virus.